Literature Study: The Effect of Animation Learning Media on Elementary School Students' Interest in Learning Mathematics - Umar, Faishal; Chusna, Alfina Zahrotul; Maulidiyah, Nur Azizatul; Fakhriyah, Fina; Fajrie, Nur (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This article aims to explore the impact of using animation media in teaching and learning activities on interest in learning mathematics among elementary school students. The method used is literature reflection on scientific articles published in the last five years (2019-2024), which can be accessed via Google Scholar . The learning media exemplified is animated videos, which can be used via various devices such as laptops, computers and Android devices to present mathematical material visually and Dynamically based on literature observations , the use of animated learning media that utilizes the latest digital technology can significantly increase students ' interest in learning. It was found that this approach made it easier for students to understand the lesson material, reduced the level of boredom , and increased their focus on absorbing learning. This approach can be adapted to current needs and developments.